2021
DOI: 10.3390/buildings11070310
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Types of Infill Walls on the Hysteretic Performance of Reinforced Concrete Frames

Abstract: To study the influence of masonry infill walls on the hysteretic performance of reinforced concrete frames, a cyclic experiment was conducted for three two-story and two-span reinforced concrete frame structures, including one reinforced concrete frame without infill walls and two frames with infill walls. Whether the infill walls were constructed in the frames and the type of infilled material were the main parameters of the test. The major results reveal that: the infill walls clearly changed the mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…The presence of window and door openings in the infill wall is also the reason it is not considered as a structural component. Meanwhile, the test results showed that the infill wall frame structure with openings is still much stiffer and stronger than the open frame structure [1], [19] and [20]. Infilled wall-frames is a structure that consists of columns and beams made of steel or reinforced concrete with walls inside them.…”
Section: Infill Wall Framementioning
confidence: 99%
“…The presence of window and door openings in the infill wall is also the reason it is not considered as a structural component. Meanwhile, the test results showed that the infill wall frame structure with openings is still much stiffer and stronger than the open frame structure [1], [19] and [20]. Infilled wall-frames is a structure that consists of columns and beams made of steel or reinforced concrete with walls inside them.…”
Section: Infill Wall Framementioning
confidence: 99%
“…The lateral strength of the exterior column can be determined by the developed analytical model by appliying the equation developed [19] obtaining the maximum values of 18.9 kN, 43.2 kN, and 31.7 kN for each testing structure of BF-2B, IF-2B-BM, and IF-2B-LM. This value is almost similar to the lateral strength of the exterior column of the test results, eq.…”
Section: Column Lateral Strengthmentioning
confidence: 99%
“…structure [14]. The use of infill walls also gave a significant contribution to the frame structure during the earthquake [15][16][17][18][19]. An analytical model of a reinforced concrete portal structure with masonry walls as a structural filler with a diagonal strut concept.…”
mentioning
confidence: 99%
“…After large deformation occurred, the compression effect of the wood column on the infill resulted in damage, such as cracks, sliding, loosening, and falling of the infill. Similar to reinforced concrete frames with the infill wall, the mud and stone infill behave strong diagonal bracing effect [40] and the damage near the top of the columns and beam-column connections occurred first. Differently, the compression damage from the timber frame resulted in the detachment of the double-layer mud and stone wall, similar to the shear of the middle layer of the infill wall in the thickness direction.…”
Section: Experimental Phenomenamentioning
confidence: 99%